Estudo da dinâmica de interação e transmissão da esquistossomose mansônica : a importância do miracídio de schistosoma mansoni - Souza, Renata Perotto de (2021)
In Brazil, the schistosomiasis mansoni has the highest focus on the Northeast region, being the local climate an important factor for the disease transmission. Of six stages of development, only the miracidia and cercariae are infectant for their respectives hosts, the snail, and humans. The schistosomiasis affects more than 200 million people, and the World Health Organization set it as a global public health problem, highlighting the need of actions to transmission’s interruption. The aim of this work is study the dynamics between S. mansoni miracidium and its intermediate host, the mollusc genus Biomphalaria, accordingly with the transmission perspective. To establish the longevity and infectivity, six types of movements were categorized, and they were observed for 10 hours in four types of environments: climatic chamber, climatic chamber without light, environment with light and environment without light. Miracidia lifespan was 3h30 and the infectivity was 2h, both parameters have not differed significantly between the four environments or environments with and without light. Using data of miracidia and snail interaction from the literature, a model to simulate their dynamics related with their populational size was built by NetLogo language. In the simulations the infected snails rate increased proportionally with the increase of miracidia and snail initial population size. Also, the magnetic field effect in miracidia movements was evaluated using a Helmholtz’s coil. The coil generated a homogeneous and local field where miracidia remained exposed for five minutes, being recorded pre-exposure, exposure, and post-exposure movements. The miracidia’s kinematics presented significative difference (p= 0.03) after exposure to Helmholtz’s coil.